Respuesta :

Answer:

x + 2y = 10 -  x= 10−2y

3x + 4y = 8   - x=8/3   -   4y/3

Step-by-step explanation:

Hibrah

x+2y=10;3x+4y=8

Solution :

{ x , y } = { -12 , 11}

System of Linear Equations entered :

[1] x + 2y = 10

[2] 3x + 4y = 8

Graphic Representation of the Equations :

2y + x = 10 4y + 3x = 8

Solve by Substitution :

// Solve equation [1] for the variable x

[1] x = -2y + 10

// Plug this in for variable x in equation [2]

[2] 3• ( -2y +10) + 4y = 8

[2] - 2y = -22

// Solve equation [2] for the variable y

[2] 2y = 22

[2] y = 11

// By now we know this much :

x = -2y +10

y = 11

// Use the y value to solve for x

x = -2(11) +10 = -12

Solution :

{ x , y } = { -12 , 11}

ACCESS MORE